Studi kasus: Mental accounting bias dan confirmation bias terhadap pengambilan keputusan investasi saham pada galeri investasi universitas - Cahyadi Husadha; Wastam Wahyu Hidayat; Devi Fitriani; Elia Rossa (LPMP Imperium, 2022)
The decision for an investor in the criteria for making stock investment decisions aims to determine the effect of mental accounting bias and confirmation bias. This study took a sample of students in an investment gallery of a private university in Bekasi. The population in this study are student investors at the Investment Gallery of Bhayangkara University, Jakarta Raya Bekasi. Data were collected through online questionnaires on students who have investment experience. The study results indicate that mental accounting and confirmation bias positively and significantly affect stock investment decision-making. This study provides insights to researchers and practitioners studying budding investors in a university setting.